EXPERIMENTAL STUDY ON SHOCK RESPONSE CHARACTERISTICS OF SLIDING BEARING WITH OIL FILM FORCE CONSIDERATION - FENG LinHan; WANG Yu; JI Chen (Jixie qiangdu)
The sliding bearing is an important component of propulsion shaft in ship; its stability is the basic promise of maneuverability. A large-sized sliding bearing on board as the subject was investigated. The experimental shafting system for simulating installation state and wording state on board was specially developed. The shock tests were carried through on floating shock platform subjected to underwater explosions. The test results showed that the rubs appeared between the bushing and shaft during intense vertical impact loading,as a result the operate moment of torque was instantly increased about 200%,which presented more requirements for shafting power. Due to the smaller intensity of transverse shock loading,the vibration amplitude was under the scope of bearing gap. Through these shock tests of sliding bearing,the dynamic model of oil film in present application does not appropriate for shock response analysis. This research presents reference for modifying shock dynamic model and increasing the simulation accuracy of shafting system.